Evaluating the implementation quality of a vocational education intervention for youth in Dadaab refugee camp in Kenya: Evidence of discrimination - Kunyu, David K.; Moreno Herrera, Lázaro; Juang, Linda P. (Frontiers in Human Dynamics, 2022)
Refugee youth in protracted humanitarian contexts are faced with limited access to quality education. They may sustain traumatic experiences from conflicts and discrimination yet have limited psychosocial support access. Comprehending the magnitude and effects of these challenges is vital for designing and executing educational interventions in such contexts. This study evaluates the implementation quality of the Youth Education Pack intervention through the lens of the Inter-agency Network for Education in Emergencies minimum standards framework. It explores the types of discrimination experienced by refugee youth in the Dadaab refugee camp in Kenya. Nine participants comprising of refugee students (N= 2), former refugee students (N= 2), teachers (N= 3), and supervisors (N= 2) participated in the study. The first author conducted interviews and observations in the camp. The data were qualitatively coded deductively and analysed in Nvivo 12. We found that the YEP intervention faced contextual challenges that hindered the achievement of the implementation quality standards outlined in the INEE minimum standards for education. Refugee youth and refugee teachers experienced various forms of discrimination, including individual, institutional, and structural levels. We conclude that providing refugee youth with an inclusive and high-quality education is central to providing secure and long-term solutions to their challenges and adversities and may promote their psychosocial well-being.